ЗАИМСТВОВАНИЕ ИНОЯЗЫЧНЫХ АББРЕВИАТУР ЭКОНОМИЧЕСКОГО ХАРАКТЕРА ЛИТЕРАТУРНЫМ АРАБСКИМ ЯЗЫКОМ - Адиханов, Д. С. (Journal of Oriental Studies, 2016)
Given article is educated to a problematic of loan of abbreviations speaking another language by the Arabian literary language. The urgency to the given problematic consists that abbreviations are not peculiar to the Arabian language. At the same time, aspiration of language to brevity and influence of English language have reached such level, that in economic sphere of the Arabian lan-guage requires abbreviations.